Survival and prognostic factors in cats with restrictive cardiomyopathy: a review of 90 cases. Issue 12 (December 2018) - Locatelli, Chiara; Pradelli, Danitza; Campo, Giulia; Spalla, Ilaria; Savarese, Alice; Brambilla, Paola G; Bussadori, Claudio
Objectives: Large studies focusing on restrictive cardiomyopathy (RCM) in the cat are scarce. The aims of this retrospective study were to describe epidemiological characteristics and to analyse prognostic factors affecting survival in cats with RCM. Methods: The clinical archives of the Gran Sasso Veterinary Clinic (Milan, Italy) and of the cardiology unit of the Department of Veterinary Medicine (University of Milan, Italy) from 1997–2015 were reviewed for all cats diagnosed with RCM based on an echocardiographic examination (left atrial/biatrial enlargement, normal left ventricle wall thickness, normal or mildly decreased systolic function and restrictive left ventricle filling pattern with pulsed Doppler echocardiography). Results: The study population comprised 90 cats (53 male, 37 female) with an echocardiographic diagnosis of RCM. Most were domestic shorthairs (n = 60) with a mean ± SD age of 10.0 ± 4.3 years and a median weight of 3.8 kg (interquartile range 3.2–5 kg). Most cats were symptomatic (n = 87). The most common clinical sign was respiratory distress (n = 75). Follow-up was available for 60 cats and the median survival time (MST) was 69 days (95% confidence interval [CI] 0–175 days). Cardiac-related death occurred in 50 cats. In the multivariate Cox analysis only respiratory distress showed a statistically significant effect on survival. The cats without respiratory distress showed an MST of 466 days (95% CI 0–1208); cats with respiratory distress showing an MST of 64 days (95% CI 8–120; P = 0.011). Conclusions and relevance: RCM can be considered an end-stage condition associated with a poor prognosis, with few cats not showing clinical signs and surviving >1 year. Most cats died of cardiac disease within a very short time.